2014
DOI: 10.1002/ejic.201402378
|View full text |Cite
|
Sign up to set email alerts
|

BOX Ligands in Biomimetic Copper‐Mediated Dioxygen Activation: A Hemocyanin Model

Abstract: The μ‐η2:η2‐peroxodicopper(II) core found in the oxy forms of the active sites of type III dicopper proteins have been a key target for bioinorganic model studies. Here, it is shown that simple bis(oxazoline)s (BOXs), which are classified among the so‐called “privileged ligands”, provide a suitable scaffold for supporting such biomimetic copper/dioxygen chemistry. Three derivatives R,HBOX‐Me2 (R = H, Me, tBu) with different backbone substituents have been used. Their bis(oxazoline)‐copper(I) complexes bind dio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 102 publications
(117 reference statements)
5
15
0
Order By: Relevance
“…CuL OL 2 and CuBIMZ were measured in dichloromethane and exhibited absorption maxima at λ = 340 nm and λ = 610 nm for CuL OL 2 and λ = 333 nm as well as λ = 600 nm for CuBIMZ. The slight shift of the π σ * → d x 2 −y 2 charge transfer transition to higher energies was also noticed for copper(I) complexes with bidentate bis(oxazoline) ligands [67]. In contrast, no µ-η 2 :η 2 -peroxo-dicopper(II) complex could be found for CuL imz 1 in tetrahydrofuran, dichloromethane, and acetone.…”
Section: Tyrosinase Activitymentioning
confidence: 79%
“…CuL OL 2 and CuBIMZ were measured in dichloromethane and exhibited absorption maxima at λ = 340 nm and λ = 610 nm for CuL OL 2 and λ = 333 nm as well as λ = 600 nm for CuBIMZ. The slight shift of the π σ * → d x 2 −y 2 charge transfer transition to higher energies was also noticed for copper(I) complexes with bidentate bis(oxazoline) ligands [67]. In contrast, no µ-η 2 :η 2 -peroxo-dicopper(II) complex could be found for CuL imz 1 in tetrahydrofuran, dichloromethane, and acetone.…”
Section: Tyrosinase Activitymentioning
confidence: 79%
“…29 By spectroscopic means we demonstrated that several ligands, R,H BOXs (Scheme 1B), reversibly bind to dioxygen to form μ-η 2 :η 2 -peroxidodicopper( ii ) complexes, both in solution and in the solid state; the thermodynamic and kinetic parameters of the P core formation have been determined. 29 Furthermore, we have shown that certain free bis(oxazoline)s, R,H BOXs, exist as an equilibrium mixture between the diimine and iminoenamine tautomers. 30 The latter are reminiscent of β-diketimines used extensively as anionic ligands after deprotonation, which led us to consider R,H BOXs as proton responsive ligands.…”
Section: Resultsmentioning
confidence: 96%
“…Reactions of R,R′ BOX with [Cu(MeCN) 4 ]ClO 4 in tetrahydrofuran (THF) gave the air sensitive copper( i ) complexes [( R,R′ BOX)Cu(MeCN)]ClO 4 , 1 (R = R′ = Me), 2 (R = Me, R′ = H), 3 (R = R′ = H) 29 as colourless compounds (see ESI†). Oxygenation of 1 , 2 and 3 in THF at 193 K led to deep purple coloured solutions of [{ R,R′ BOX(THF)Cu} 2 (μ-η 2 :η 2 -O 2 )](ClO 4 ) 2 , P 4 (R = R′ = Me), P 5 (R = Me, R′ = H) and P 6 (R = R′ = H) with intense optical features around 330 nm ( ε ≈ 20 × 10 3 M –1 cm –1 ) and 500 nm ( ε ≈ 1 × 10 3 M –1 cm –1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations